Resistant discourse strategies in social media in China’s epidemic prevention context - Li, Yang (Discourse & society, 2025)
On the night of November 24, in 2022, a fire broke out in a residential building in Xinjiang Urumqi, causing 10 deaths and 9 injuries. Confronted with netizens’ queries about excessive epidemic prevention, local government quickly disclaimed and announced its political achievements in fighting against COVID-19. A participatory discourse of resistance in social media then broke out intensively during the 25–28th, which extended too offline and then back to online again. There are three questions this study aims to investigate: (1) What were the strategic characteristics exhibited by this discourse event? (2) How did the concealed socio-political factors operate? (3) Does a prevailing ideological configuration pattern manifest in practice and what is the role of social media? In order to comply with the digital discourse context deeply embedded by platform’s technology, this study followed KhosraviNik’s three-level theoretical framework, whose SM-CDS model was methodologically employed and 9 actors with 10 samples were grabbed, concluding that an independent space of resistant meaning’s production was opened up at the angle of coding rules operated in social media and by authority, where a special discourse pattern was developed. In phase Ⅰ, it displayed ‘strategized’ consisted of three strategies: (1) obscuring the meaning; (2) applying positive words; and (3) seeking for asylum. In phase Ⅱ, it inclined to be ‘de-strategized’ which eventually shed the dependence on the coding rules of both authority and social media, which is a breakthrough to the previous resistant discourse patterns. Through netizens’ strategic utilization of availability and visibility, the technical ideology of social media fully exposes its constructive significance to the democratic space, making the negotiation of meaning obtain more extension, flexibility, and resilience.